RanGTP and importin β regulate meiosis I spindle assembly and function in mouse oocytes - Drutovic, David; Duan, Xing; Li, Rong; Kalab, Petr; Solc, Petr (EMBO journal, 2020)
Homologous chromosome segregation during meiosis I (MI) in mammalian oocytes is carried out by the acentrosomal MI spindles. Whereas studies in human oocytes identified Ran GTPase as a crucial regulator of the MI spindle function, experiments in mouse oocytes questioned the generality of this notion. Here, we use live-cell imaging with fluorescent probes and Förster resonance energy transfer (FRET) biosensors to monitor the changes in Ran and importin β signaling induced by perturbations of Ran in mouse oocytes while examining the MI spindle dynamics. We show that unlike RanT24N employed in previous studies, a RanT24N, T42A double mutant inhibits RanGEF without perturbing cargo binding to importin β and disrupts MI spindle function in chromosome segregation. Roles of Ran and importin β in the coalescence of microtubule organizing centers (MTOCs) and MI spindle assembly are further supported by the use of the chemical inhibitor importazole, whose effects are partially rescued by the GTP hydrolysis-resistant RanQ69L mutant. These results indicate that RanGTP is essential for MI spindle assembly and function both in humans and mice.
Keywords: výměnné faktory guaninnukleotidů; proteiny buněčného cyklu; beta karyoferiny; aparát dělícího vřeténka; oocyty; Mutation; mikrotubuly; Mice; Spindle Apparatus; zvířata; ran GTP-Binding Protein; segregace chromozomů; Nuclear Proteins; ran protein vázající GTP; jaderné proteiny; Oocytes; Microtubules; meióza; Meiosis; beta Karyopherins; Chromosome Segregation; Cell Cycle Proteins; Guanine Nucleotide Exchange Factors; myši; ženské pohlaví; Animals; mutace; Female